A versatile and useful template method for skin graft harvesting and applying [Deri grefti uygulamasini kolaylaştiran basit ve kulanişli bir kalip yöntemi] - (:unkn) unknown (My University, 2011)
As an indispensable step on the reconstructive ladder, skin graft is one of the oldest and most frequently applied methods in plastic and reconstructive surgery for the closure of various defects which cannot be closed primarily. Due to the difficulty of the skin grafts' manipulation owing to its delicate structure and due the time consuming nature of its shaping and adaptation to the defect, we have developed a new and inexpensive template which can accelerate the skin grafting procedure and improve the overall matching of the skin graft to the defect.
Keywords: Full-thickness; Inexpensive; Skin graft; Split-thickness; Template